Assessment of the Implementation Level and Gaps in the Disaster-Resilient Neighborhood Program (KALTANA) in Supporting Relevant Sustainable Development Goals (SDGs) in Cirebon City - Syaikha Alya Rizqilla; Mohd. Abi Rafdi (Salus Publica: Journal of Community Service, 2026)
he Disaster-Resilient Neighborhood Program (KALTANA) is one of the Community-Based Disaster Risk Reduction (CBDRR) strategies developed by the National Disaster Management Agency (BNPB) to enhance community capacity in facing disaster threats. Meanwhile, the Sustainable Development Goals (SDGs) identify disaster resilience as a key aspect of achieving sustainable development. The KALTANA Program has been implemented in 12 neighborhoods in Cirebon City; however, the extent to which its implementation supports the achievement of relevant SDG goals and targets still requires evaluation. This study aims to assess the level of implementation and gaps in the KALTANA Program in supporting the achievement of relevant SDGs at the neighborhood level in Cirebon City. This study employs a descriptive qualitative approach using data collection techniques such as in-depth interviews, document analysis, and a literature review. Analysis was conducted through data reduction, data presentation, assessment of the implementation level of KALTANA indicators, and an analysis of gaps relative to relevant SDG targets. The results indicate that the implementation of the KALTANA Program in Cirebon City has been carried out across the entire study area. However, the level of implementation is not yet uniform. Differences in implementation are influenced by institutional capacity, the availability of disaster-related facilities and infrastructure, community participation, and the continuity of program guidance. The implementation of KALTANA indicators contributes to supporting several SDGs, particularly SDG 11 (Sustainable Cities and Communities) and SDG 13 (Climate Action). However, there remains a gap between the actual implementation conditions on the ground and the sustainable development targets. Therefore, it is necessary to strengthen coordination among stakeholders, enhance capacity, and provide continuous program guidance so that the implementation of KALTANA can make a more optimal contribution to achieving the SDGs at the urban village level.